Interpreting Masonry Wall Cracking through Moisture-Induced Ground Movement and Soil–Structure Interaction in Fine-Grained Soils - Fachri Fachri; Jumelia Ardika; Reza Pahlevi Munirwan; Munawir Munawir; Fitri Zaitun Nurnalisa (INSOLOGI: Jurnal Sains dan Teknologi, 2026)
This study investigates low rise construction located in Aceh Besar, Aceh Province – Indonesia, with shallow strip masonry foundation system exhibiting wall cracking on their wall sections. The damage is suspected caused by the shrink – swell behaviour in fine-grained moisture sensitive soil. Laboratory testing was conducted to obtain soil properties including water content, unit weight, Atteberg Limits and sieve analysis for soil gradation. Further, by using the soil mechanic framework, the analysis shows that seasonal change in moisture content leads to shrink-swell behaviour and volumetric change. The volumetric change was spatially non-uniform causing differential local movement in the supporting ground beneath foundation. The observed crack patterns are in agreement with this local ground settlement inducing tensile stress in masonry infill wall due to this differential movement of ground support. The findings reflect that even soil with moderate plasticity and activity can caused significant structural stress upon subjected to drying-wetting cycle. The study also indicates that the main cause of this damage is the incompatibility between supporting ground with the above rigid body of structure due to non-uniformity volumetric change in supporting ground induced by shrink-swell behaviour of soil. In general, several essential things to highlight for this study are environmental condition change, soil behaviour and structural response/soil structure interaction in low rise construction with shallow foundation system.